2018
DOI: 10.1177/0013124518785444
|View full text |Cite
|
Sign up to set email alerts
|

Collective Expectations Protecting and Preventing Academic Achievement

Abstract: High academic expectation—how far a student expects to get in school—is usually predictive of positive outcomes for a student. Yet less is known about mechanisms behind collective expectation: the proportion of students in a school who expect to pursue further studies. Using urban schools’ data from the Education Longitudinal Study 2002, this research examines how collective expectations affect short-term and long-term outcomes, and the predictors of these expectations. Through hierarchical linear models, I fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
(75 reference statements)
1
5
0
Order By: Relevance
“…Such a framework exerts pressure upon individual students to conform to the norm of higher education enrolment. Therefore, in line with the results of Trinidad (2018), we hypothesize that attending secondary schools with a higher expectation culture leads to higher chances to enrol in higher education.…”
Section: From An Individualistic Account To Student Culturesupporting
confidence: 73%
See 3 more Smart Citations
“…Such a framework exerts pressure upon individual students to conform to the norm of higher education enrolment. Therefore, in line with the results of Trinidad (2018), we hypothesize that attending secondary schools with a higher expectation culture leads to higher chances to enrol in higher education.…”
Section: From An Individualistic Account To Student Culturesupporting
confidence: 73%
“…In fact, different theoretical models on college enrolment identify students' post-secondary expectations in secondary education as the first step towards higher education enrolment (Hossler et al, 1989;Perna, 2006). Empirical research, furthermore, confirms that post-secondary expectations affect higher education enrolment (Bates and Anderson, 2014;Hill and Wang, 2015;Trinidad, 2018). While initial studies mostly looked at students' aspirationsthe education a student desires to attain -, later research showed expectationsthe education one expects to attainto be a better predictor of enrolment (Hanson, 1994).…”
Section: The Significance Of (Peers') Educational Expectationsmentioning
confidence: 79%
See 2 more Smart Citations
“…Educational inequalities are constructed by specific conditions around and within a school, as schools play an essential role in equal opportunities, processes, and outcomes (Oppedisano & Turati, 2015;Trinidad, 2019). This article explores the Norwegian context and the challenges identified as unequal opportunities in education, specifically focusing on how school personnel address inequality and work to counteract exclusion.…”
Section: Introduction To Inequality In Nordic Schoolsmentioning
confidence: 99%